Impact of high salinity and the compatible solute glycine betaine on gene expression of Bacillus subtilis. (8th June 2020) - Rath, Hermann; Sappa, Praveen K.; Hoffmann, Tamara; Gesell Salazar, Manuela; Reder, Alexander; Steil, Leif; Hecker, Michael; Bremer, Erhard; Mäder, Ulrike; Völker, Uwe
Summary: The Gram‐positive bacterium Bacillus subtilis is frequently exposed to hyperosmotic conditions. In addition to the induction of genes involved in the accumulation of compatible solutes, high salinity exerts widespread effects on B. subtilis physiology, including changes in cell wall metabolism, induction of an iron limitation response, reduced motility and suppression of sporulation. We performed a combined whole‐transcriptome and proteome analysis of B. subtilis 168 cells continuously cultivated at low or high (1.2 M NaCl) salinity. Our study revealed significant changes in the expression of more than one‐fourth of the protein‐coding genes and of numerous non‐coding RNAs. New aspects in understanding the impact of high salinity on B. subtilis include a sustained low‐level induction of the SigB‐dependent general stress response and strong repression of biofilm formation under high‐salinity conditions. The accumulation of compatible solutes such as glycine betaine aids the cells to cope with water stress by maintaining physiologically adequate levels of turgor and also affects multiple cellular processes through interactions with cellular components. Therefore, we additionally analysed the global effects of glycine betaine on the transcriptome and proteome of B. subtilis and revealed that it influences gene expression not only under high‐salinity, but also under standard growth conditions.